MPME- Qual o tratamento mais adequado - regime diferenciado como forma de redução da informalidade? - Marcelo, Edson Luiz Fernandes (2005)
This project analyzes the role of micro, small and medium companies in Brazil, their importance in generation of income and job and compares the main economic indicators of this segment with the ones of other countries. The work encompasses an analysis of the main problems that turns the development of these companies so difficult. It also evidences what has been done and what is being done to change that situation and suggests that public policies should prioritize the improvement of their competitiveness through the reduction of the obstacles caused by the unnecessary regulation, difficulties in accessing financial programs whether of medium or long terms and through programs and incentives aiming the improvement of companies management. The importance and the evolution of the Industrial Districts in Brazil is put in evidence, since it is considered by many authors as an alternative to the strengthening of the micro, small and medium companies and regional development. An analysis of the main indicator of informal economy is presented in this work. It also investigates how some specific public policies could cause the reduction of the current levels of informality. The dissertation concludes reaffirming the principal actions that could be prioritized in different and distinct areas - regulation, judiciary, tax, credit, all objectifying the improvement of productivity of the micro, small and medium companies.